Bright to Dim Oscillatory Response of the Neurospora Circadian Oscillator. (February 2014) - Gooch, Van D.; Johnson, Alicia E.; Larrondo, Luis F.; Loros, Jennifer J.; Dunlap, Jay C.
The fungus Neurospora crassa constitutes an important model system extensively used in chronobiology. Several studies have addressed how environmental cues, such as light, can reset or synchronize a circadian system. By means of an optimized firefly luciferase reporter gene and a controllable lighting system, we show that Neurospora can display molecular circadian rhythms in dim light when cultures receive bright light prior to entering dim light conditions. We refer to this behavior as the "bright to dim oscillatory response" (BDOR). The bright light treatment can be applied up to 76 h prior to dim exposure, and it can be as short as 15 min in duration. We have characterized this response in respect to the duration of the light pulse, the time of the light pulse before dim, the intensity of dim light, and the oscillation dynamics in dim light. Although the molecular mechanism that drives the BDOR remains obscure, these findings suggest that a long-term memory of bright light exists as part of the circadian molecular components. It is important to consider the ecological significance of such dim light responses in respect to how organisms naturally maintain their timing mechanism in moonlight.